THE INFLUENCE OF AGGREGATE SIZE AND COMPACTION ON VOID CONTENT AND COMPRESSIVE STRENGTH OF PREVIOUS CONCRETE - Powerija, Ing Cahya; Sutandar, Erwin; Supriyadi, Asep (Fakultas Teknik Universitas Tanjungpura, 2024)
Pervious concrete is one of the alternatives to prevent flooding during the rainy season. Because of the large number of pores produced by the absence or use of fine aggregate in its production, previous concrete has a poor compressive strength. This study focuses on the size and manner of compaction of coarse aggregates to boost the compressive strength of previous concrete. It is essential to address the void content in this process. The research started by analyzing the materials used to make the previous concrete mix. The next step was to determine the void content, plan the mix design, make the mix, treat the concrete, and finally test it using various methods such as volume weight, compressive strength, porosity, and permeability tests. Research shows that a three-layer perforated variation on a 0.5/0.5 cm coarse aggregate with a compressive strength of 21.04 MPa, volume weight of 1896.674 kg/m3, permeability of 0.597 cm/s, and porosity of 16.232% yields the best results. Although 24 MPa was the intended compressive strength, previous concrete fell short due to the paste content used in the compaction method. In addition, the volume weight is lighter than the plan, and the permeability and porosity are more significant than the plan. The relationship between aggregate size and compaction method is based on the graph of the effect of void content and paste content, which shows that the greater the paste content, the smaller the void content produced.